INVESTIGATION OF EROSION PROTOTYPES ELECTRICAL CONTACT - DETAILS ON THE BASIS SILVER AND COPPER - Mrachkovskyy, A. (Energy and Automation, 2016)
Research and received electric erosion patterns of change on contact - detail relay type HRC - 2204, made from composite material based on silver and copper, depending on the structure of the material, its physical - mechanical properties and phase components in the surface layer of the working surface contact details.